Poly (I:C) therapy decreases cerebral ischaemia/reperfusion injury via TLR3‐mediated prevention of Fas/FADD interaction. Issue 3 (29th October 2014) - Zhang, Xia; Ha, Tuanzhu; Lu, Chen; Lam, Fred; Liu, Li; Schweitzer, John; Kalbfleisch, John; Kao, Race L.; Williams, David L.; Li, Chuanfu
Abstract Toll‐like receptor (TLR)‐mediated signalling plays a role in cerebral ischaemia/reperfusion (I/R) injury. Modulation of TLRs has been reported to protect against cerebral I/R injury. This study examined whether modulation of TLR3 with poly (I:C) will induce protection against cerebral I/R injury. Mice were treated with or without Poly (I:C) (n = 8/group) 1 hr prior to cerebral ischaemia (60 min.) followed by reperfusion (24 hrs). Poly (I:C) pre‐treatment significantly reduced the infarct volume by 57.2% compared with untreated I/R mice. Therapeutic administration of Poly (I:C), administered 30 min. after cerebral ischaemia, markedly decreased infarct volume by 34.9%. However, Poly (I:C)‐induced protection was lost in TLR3 knockout mice. In poly (I:C)‐treated mice, there was less neuronal damage in the hippocampus compared with untreated I/R mice. Poly (I:C) treatment induced IRF3 phosphorylation, but it inhibited NF‐κB activation in the brain. Poly (I:C) also decreased I/R‐induced apoptosis by attenuation of Fas/FasL‐mediated apoptotic signalling. In addition, Poly (I:C) treatment decreased microglial cell caspase‐3 activity. In vitro data showed that Poly (I:C) prevented hypoxia/reoxygenation (H/R)‐induced interaction between Fas and FADD as well as caspase‐3 and ‐8 activation in microglial cells. Importantly, Poly (I:C) treatment induced co‐association between TLR3 and Fas. Our data suggest that Poly (I:C) decreases in cerebral I/R injury via TLR3 which associates with Fas, thereby preventing the interaction of Fas and FADD, as well as microglial cell caspase‐3 and ‐8 activities. We conclude that TLR3 modulation by Poly (I:C) could be a potential approach for protection against ischaemic stroke.